Government expenditure and health, education and housing outcomes: empirical analysis from South Africa - Mbatha, Michael (Graduate School of Business (GSB), 2025)
This study analyses the relationship between government expenditure on health, education, and housing and their corresponding outcomes across nine provinces in South Africa. Notwithstanding considerable public investment in these vital areas, South Africa persists in confronting serious difficulties, such as elevated infant and TB mortality rates, enduring HIV prevalence, inadequate educational achievement, and a substantial housing deficit. These challenges prompt enquiries into the efficiency and efficacy of public expenditure and its congruence with developmental aims. The study utilised panel data from nine provinces between 2004 and 2019, employing fixed and random effects models to examine the influence of government expenditure on sector-specific outcomes. The findings indicate that health expenditure has a positive, statistically insignificant impact on health outcomes, such as infant mortality, TB mortality, and HIV prevalence. Conversely, education expenditure had a negative and statistically significant correlation with educational outcomes, as indicated by senior certificate results, learner-school ratios, and educator-school ratios, underscoring potential inefficiencies and mismatched fiscal objectives. Housing expenditure was determined to have a positive and statistically significant effect on housing outcomes, particularly the total quantity of housing units supplied. The findings indicate that although government investment in housing produces concrete advantages, inefficiencies in health and education funding obstruct the achievement of intended objectives. The study findings highlight the necessity for improved resource allocation, focused interventions, and enhanced monitoring systems to ensure public spending result in substantial advancements in societal well-being.